Results of surgery for late sequelae of cicatricial retinopathy of prematurity - Atalay, Hatice; Özdek, Şengül; Yalınbaş, Duygu; Özsaygılı, Cemal; Özmen, Mehmet (Indian journal of ophthalmology, 2019)
Purpose: To report anatomical and functional results of vitreoretinal surgery in our case series of late cicatricial retinopathy of prematurity (ROP) patients with subtotal retinal detachment. Methods: This is a retrospective, consecutive case series. Eleven eyes of 10 patients presented with partial tractional retinal detachment secondary to late cicatricial ROP (cicatricial stage 4B) who underwent vitreoretinal surgery were retrospectively reviewed. Anatomical and functional outcomes were evaluated. Results: The mean gestational age at birth was 28.6 (26-32) weeks. The mean age at surgery was 79 (4-213) months. Patients were followed up for 21.7 (6-40) months. Six eyes (55%) had lens-sparing vitrectomy and five eyes (45%) had lensectomy + vitrectomy. Anatomical success was achieved in 10 eyes (91%). Improvement in visual acuity was noted in nine eyes (82%). Conclusion: Eye grows but fibrotic tissue does not grow with age, and during this period retinal traction may get worse. Relieving these tractions may lead to good anatomical and visual outcomes in selected late cicatricial ROP cases.